Toward a Model of Personality Competencies Underlying Social and Emotional Skills: Insight From the Circumplex of Personality Metatraits - Cieciuch, Jan; Strus, Włodzimierz (Frontiers in Psychology, 2021)
In recent years, there has been a growing interest in social and emotional skills both in the scientific literature, as well as in social practice. The paper presents an overview of the ways of understanding what social and emotional skills are and the catalogs thereof. There are some attempts in the literature to organize these catalogs within the Big Five traits that for a long time was claimed to be the most sound model of basic orthogonal dimensions of personality. However, further research on personality structure revealed that two metatraits can be found above the Big Five traits. These two metatraits form the basis of the Two Factor Model of personality, which was later developed into the Circumplex of Personality Metatraits. It turned out that in certain aspects models based on metatraits have a greater theoretical potential than those based on the Big Five traits. The paper presents a proposal for describing social and emotional skills from the perspective of the Circumplex of Personality Metatraits rather than the Big Five. In this framework, we distinguish the concept of personality competences that underlay and organize many specific social and emotional skills and identify the core personality competencies on the basis of the Circumplex of Personality Metatraits model.